Laplace DLTS study of the fine structure and metastability of the radiation-induced E3 defect level in GaAs. (5th November 2018) - Taghizadeh, F; Ostvar, K; Auret, F D; Meyer, W E
Abstract: In this paper we used high-resolution Laplace deep-level transient spectroscopy (DLTS) to study the electrical properties of the E3 defect family introduced in GaAs by MeV electron irradiation. We found that the peak conventionally referred to as the E3 contained 3 components which we labeled E3a, E3b and E3c, with E3a being the most prominent component. The activation energy of E3a for different carrier densities varied between 0.36 and 0.375 eV. From dopant dependent introduction rate measurements, we found that the introduction rates of the E3a and E3b defect did not depend on doping density. However, the E3c concentration increased with increasing carrier density. Furthermore, the E3c was found to be metastable: it was reversibly removed during minority carrier injection at low temperatures and re-introduced by annealing above 160 K under zero bias. Interestingly, annealing measurements revealed that, of the three components, the E3b annealed first at around 500 K while both the other components annealed together at a higher temperature of 525 K. By comparing our results with previous studies, we concluded that the origin of E3a is VAs, E3b is Asi and E3c is VGa –SiGa .